2008
DOI: 10.1021/jp807471e
|View full text |Cite
|
Sign up to set email alerts
|

The Chromophore Structure of the Cyanobacterial Phytochrome Cph1 As Predicted by Time-Dependent Density Functional Theory

Abstract: The UV-vis absorption spectra of the photoreceptor chromophores biliverdin (BV) in the ZZZssa conformation and the phycocyanobilin (PCB) with conformations ZZZssa and ZZZasa have been investigated by means of time-dependent density functional theory (TD-DFT) with a polarized continuum model. The three systems are studied in different conditions to include protonation, solvation- and protein-environmental effects on gas phase and available X-ray structures. The crystal structures of BV in bacteriophytochrome of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 40 publications
(70 reference statements)
5
39
0
2
Order By: Relevance
“…43 While calculation of the full spectra would offer further insight into the photochemistry of bilins, we believe that focusing on the S 1 state is a more appropriate approach because previous studies have demonstrated that no other excited state is involved in the photoisomerizations under investigation, 25,49,50 although the character of the state may change during the final stages of the reactions. 50 That TD-DFT performs well for this state, which has also been reported by other authors, 51,52 is not surprising given that the state has singleexcitation ππ* character and the same charge distribution between the pyrrole rings as the ground state 25,53 not only at chromophore geometries close to the Franck-Condon (FC) region, but also at torsionally distorted chromophore geometries. 25,53 The inability of conventional TD-DFT methods to treat excited states with appreciable charge-transfer character 54,55 is therefore of no significance for the present study.…”
Section: Assessment Of Quantum Chemical Methodologysupporting
confidence: 82%
“…43 While calculation of the full spectra would offer further insight into the photochemistry of bilins, we believe that focusing on the S 1 state is a more appropriate approach because previous studies have demonstrated that no other excited state is involved in the photoisomerizations under investigation, 25,49,50 although the character of the state may change during the final stages of the reactions. 50 That TD-DFT performs well for this state, which has also been reported by other authors, 51,52 is not surprising given that the state has singleexcitation ππ* character and the same charge distribution between the pyrrole rings as the ground state 25,53 not only at chromophore geometries close to the Franck-Condon (FC) region, but also at torsionally distorted chromophore geometries. 25,53 The inability of conventional TD-DFT methods to treat excited states with appreciable charge-transfer character 54,55 is therefore of no significance for the present study.…”
Section: Assessment Of Quantum Chemical Methodologysupporting
confidence: 82%
“…Upon red‐light absorption the Pr chromophore undergoes a rapid Z / E isomerization at the C15 methine bridge, finally resulting in a ZZEssa stereochemistry of the Pfr chromophore . Both primary light induced reactions involve several excited‐state intermediates and evolve on a picosecond time scale, typically with a “slow” Pr reaction (30–100 ps or longer) and a “fast” Pfr reaction (a few ps) .…”
Section: Introductionmentioning
confidence: 99%
“…[13] Upon red-light absorption the Pr chromophoreu ndergoes ar apid Z/E isomerization at the C15 methine bridge, finally resultingi naZZEssa stereochemistry of the Pfr chromophore. [14][15][16][17][18][19] Both primary light induced reactions involve several excited-state intermediates and evolve on ap icosecond time scale, typically with a" slow" Pr reaction (30-100 ps or longer) [20][21][22][23][24][25][26][27][28][29][30][31] and a" fast" Pfr reaction (a few ps). [20,21,23,30,[32][33][34] The photoinduced Pr half-cycle is characterizedb yt he first electronic ground-state intermediate lumi-R (already in ZZE configuration) with red-shifted absorption spectrum and consecutive, thermally driven reaction steps on the ms-to-ms time scale involving meta-Ra, meta-Rc and finally Pfr.…”
Section: Introductionmentioning
confidence: 99%
“…: AnPixJg2, [9,[13][14][15]17,18,23,24] NpR6012g4, [12,16,30,[20][21][22][25][26][27][28][29] and Slr1393g3. [31][32][33][34] However, computational studies of the spectral tuning in this CBCR family and other related bilinbinding photoreceptors are rare [35][36][37][38] although the hybrid quantum mechanics/molecular mechanics (QM/MM) methodology has provided valuable insight into the spectral tuning of other photoreceptor protein families with isomerizable double bonds. [19,[39][40][41] The simulations performed so far for CBCRs are either classical molecular dynamics of the protein [15,24] or excited state quantum chemical calculations on isolated chromophores.…”
mentioning
confidence: 99%